Cal Poly Memorial service for Dr. Martin Luther King, Jr. (1968)
On Monday, April 10, 1968, Cal Poly held a memorial service for Dr. Martin Luther King. The memorial was held at the Dexter Lawn and there was an estimated 1,500 students, faculty, and administrators in attendance. There is coverage of the event in the April 10, 1968 Mustang Daily. Associated Student Body president Rush Hill also spoke, the invocation was given by Rev. John Fuller and the benediction by Ref. Clarence Harms. [00:00:00] Opening prayer [00:01:55] Cal Poly President Robert E. Kennedy addresses the audience about ideas of equality [00:04:50] Song performed, 'The Love of God' by Springfield Baptist Church Choir of San Luis Obispo [00:10:36] Unidentified speaker [00:11:00] Moment of silent prayer [00:12:00] Introduction by Cay Abayo, representative from Black Student Alliance [00:13:30] Cay Abayo introduced Reverend Doctor C. Albert Henson [00:27:40] Abayo introduces another number from the choir [00:28:35] Choir begins to play [00:34:20] President of African Student Association Obediah Sam Butscher addresses audience about awareness for MLK's nonviolent efforts [00:43:05] Preston Dixon, chairman of the Black Students Alliance, speaks--emphasizes white America's role in the assassination of Dr. King. [00:50:00] Dixon wants to introduce Black curriculum in CSU system [00:53:50] Dixon speaks about the Black Student Alliance [00:56:00] Emcee thanks speaker [00:56:25] Beginning of benediction